GAMBARAN RISIKO PENYAKIT JANTUNG ANTARA KELOMPOK VEGETARIAN DAN NON-VEGETARIAN - Wira Dharma, I Bagus Putu Jaya; Suarningsih, Ni Kadek Ayu; Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024DO - 10.24843/coping.2024.v12.i04.p09, 2025)
High consumption of vegetables and fruit in vegetarians is often associated with a lower risk of disease. However, a vegetarian has the risk of lacking nutritional vitamin B12 which has the potential to accelerate the process of atherosclerosis. The risk of developing atherosclerosis also occurs in non-vegetarians who consume foods containing excessive amounts of added saturated fat. If this happens over a long period of time it will cause heart disease. This study aims to determine the risk of heart disease in vegetarian and non-vegetarian groups. The sampling technique used in this research was total sampling with crossmatch based on age and gender. Total of 60 respondents were involved in this research, divided into 30 vegetarian respondents at Sri Radha Madhava Ashram and 30 non-vegetarian respondents at BRIDA Gianyar. The risk of heart disease was evaluated using the World Health Organization International Society of Hypertension South East Asian Regional B questionnaire chart. The results of this study found that all respondents (100%) in both groups, namely vegetarians and non-vegetarians, had a risk of heart disease <10% for 10 years coming. This shows that the risk of heart disease is low. These results may be influenced by the consumption patterns of the vegetarian group on a lacto-vegetarian diet and not measuring cholesterol levels. Future researchers are expected to be able to examine the risk of heart disease in groups with all types of vegetarians and measure cholesterol levels.